Enriched environment prevents chronic stress-induced spatial learning and memory deficits - Wright, Ryan L.; Conrad, Cheryl D. (Behavioural brain research, 2008)
Chronic stress impairs spatial memory and alters hippocampal structure, which are changed in the opposite direction following enriched environment (EE). Therefore, this study incorporated these two paradigms to determine whether EE would prevent chronic stress from impairing spatial learning and memory. Young adult male rats were housed in EE for 1 week prior to and throughout 3 weeks of daily restraint stress. On the day after the end of restraint, rats were trained and tested on either a water maze (19 °C or 24 °C water temperature) or a spatial recognition Y-maze (4-h and 1-min delay between training and testing). Chronically stressed rats housed in standard conditions showed impaired acquisition on the 19 °C version of the water maze and deficits on the 4-h delay version of the Y-maze. Chronically stressed rats housed in EE, however, showed intact performance on all tasks. All rats showed intact performance on the 24 °C version of the water maze and on water maze probe trials for both versions. The results showed that EE in adulthood prevented spatial learning and memory impairment in chronically stressed rats, indicating that the context of stress exposure impacts susceptibility to chronic stress-induced cognitive deficits.